Penerapan discovery learning untuk meningkatkan keaktifan dan hasil belajar materi program linear - Edy Suwanto (Action Research Journal, 2021)
This study aims to determine the increase in student activity and learning outcomes in Linear Program material through the application of discovery learning learning models. This research was conducted at SMA Negeri 1 Karangrayung, Grobogan Regency, Central Java Province. This research method uses classroom action research with two cycles. Each cycle consists of four stages which include action planning, action implementation, observation of action results, and reflection of action results. The results showed that the average score of student learning activity in the initial conditions was 27.67 (=55.33%) then in the first cycle was 29.83 (=59.67%) and in the second cycle was 38.33 (= 76.67%. While the average value of student learning outcomes in the initial conditions was 65.87 then in the first cycle was 68.77 and in the second cycle was 75.50. The percentage of students' learning completeness in the initial condition is 10.00%, then in the first cycle it is 46.67% and in the second cycle it is 96.67%. Based on the results of the study, it can be concluded that the discovery learning model can increase the activeness and learning outcomes of students in the Linear Program material.